Analytical research for marriage delay in South Korea - Yoon Donghun (Journal of Economic and Social Development (Varaždin), 2023)
In existing research, the analysis of the cause of marriage delay has been focused on the educational level. Marriage influences the housing price because it increases housing demand. Also, it has greatly influenced the labor market participation of women. Marriage delay is the major factor of birthrate decrease because it decreases the child-bearing period and the possibility of childbearing in women. Finally, it is the major factor of the rate of decrease of the population and of economic growth. In this paper, we discuss the economic capacity as well as the educational level for the exact cause analysis. The purpose of this paper is cause analysis for marriage delay of singles in South Korea. We expect this research to propose new values for the government policy-making on marriage and birthrates through analysis of reasons for the delay in marriage. In this paper, we used the Korea Labor & Income Panel data (2004-2014). The survey was conducted among 500 men and women aged 20 to 40 through a marital status check for the last 10 years. In this study, we used estimation method and non-parametric statistics. In this paper, independent variables are the age, number of siblings, the metropolis residence, the economic level of family, the education level, the income, and the employment status. The dependent variable is the delay of marriage. Marriage encouragement is needed for birthrate increase. Also, analysis of the cause of the marriage delay of singles is essential for government policy-making. In this research, the sociocultural effect, the educational level, the economic capacity have been considered for the analysis of the cause of marriage delay. Also, we discussed the economic capacity as well as the educational level for the exact cause analysis.